Cyberattack: Cyberbullying Impact on LGBT Teenager’s Mental Health and the Way to Deal with it - Aldi Hartanto (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This thesis discusses cyberbullying impact on LGBT teenager’s mental health and the way to deal with it. The objective is to bring awareness to the readers about the issue and hopefully it could bring a better change to the society. To do so, this thesis will use cyberbullying concept to explain the definition and its negative impact, and a thesis journal to explain things that the cyberbullying victim can do to deal with cyberbullying impact. Moreover, the ‘findings’ of this thesis will be presented in screenplay. It starts with a story about a high school boy named Jonathan who becomes the victim of cyberbullying after his sexual orientation got exposed on the school anonymous gossip blog. As a result, He is suffering from mild depression. Luckily, in the end, he can find confidence within himself that it makes him has the courage to fight back against his bullies.